Development of home network sustainable interface tools - Hamid, Erman; Bahaman, Nazrulazhar; Jaafar, Azizah; Ang, Mei Choo; Abdul Malek, Akhdiat (The Science And Information Organization, 2019)
The home network has become a norm in today's life. Previous studies have shown that home network management is a problem for users who are not in the field of network technology. The existing network management tools are far too difficult to understand by ordinary home network users. Its interface is complex, and does not address the home user's needs in their daily use. This paper presents an interactive network management tool, which emphasizes support features for home network users. The tool combine interactive visual appearance with persuasive approach that support sustainability. It is not only understandable to all categories of home network users, but also acts as a feature for the user to achieve usability.